Dysregulated cytokine profile associated with biochemical premature ovarian insufficiency. (26th June 2020) - Liu, Peihao; Zhang, Xiruo; Hu, Jingmei; Cui, Linlin; Zhao, Shidou; Jiao, Xue; Qin, Yingying
Abstract: Problem: Premature ovarian insufficiency (POI) imposes great challenge on female reproduction. Whether immune disturbance in ovarian environment was implicated in POI remains unclear. We aimed to characterize the cytokine profile in follicular fluid (FF) and paired serum in patients with biochemical POI (bPOI). Method of study: Multiplex immunoassay containing 45 cytokines was performed for individual FF and paired serum samples from 35 bPOI patients and 37 matched controls. Cytokine profiles were compared between the two groups and cytokines correlated to ovarian reserve, and the rates of day‐3 good‐quality embryos were further analyzed. Results: In FF, significantly elevated level of chemokines MIP‐1α ( P  = .043), CXCL8 ( P  = .024), IP‐10 ( P  = .041), and eotaxin‐1 ( P  = .015) as well as growth factors VEGF‐D ( P  = .047), BDNF ( P  = .043), LIF ( P  = .002), and bFGF ( P  = .046) was found in bPOI patients compared to controls. Yet RANTES manifested an opposite trend with reduced levels among bPOI patients ( P  = .006). All these chemokines and growth factors in FF were significantly correlated with ovarian reserve ( P  < .05). In paired serum, cytokine signature was not likely accordant with that in FF between two groups, except for increased IP‐10 ( P  = .032) in bPOI patients and its significant correlation to FSH and AFC ( P  < .05). Among all differentially expressed cytokines, RANTES in FF was correlated with the rate of day‐3 good‐quality embryos ( P  = .035). Conclusion: Altered cytokine profile characterized by increased chemokines and growth factors was associated with early stage of POI, which may fuel the progression of the disease or even play a crucial role in the development of ovarian insufficiency.